1991
DOI: 10.1007/bf00315213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gentamicin pharmacokinetic profiles induced by mechanical ventilation

Abstract: The influence of controlled mechanical ventilation (CMV) on the pharmacokinetic profile of gentamicin has been examined in 23 patients after elective open heart surgery. A parallel design was adopted in two groups of patients; 13 patients requiring CMV for at least 32 h after surgery, all of whom were able to breath spontaneously (SB) after 72 h (study group), and 10 patients who required CMV for only a brief period and who showed SB at 32 h postsurgery. Haemodynamic parameters remained stable throughout the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
3
11
1
1
Order By: Relevance
“…In such patients, the pharmacokinetics is altered both in terms of distribution (sepsis itself can modify the V d , resuscitation measures and nutritional factors) and of elimination (drains, altered metabolism and clearance changes). The higher V d in the initial phase of sepsis has been previously described in studies on aminoglycosides [32,33] and vancomycin [34]. We recently demonstrated an increased V d and a high variability of serum antibiotic concentrations in ICU patients with severe sepsis and septic shock [14].…”
Section: Discussionmentioning
confidence: 68%
“…In such patients, the pharmacokinetics is altered both in terms of distribution (sepsis itself can modify the V d , resuscitation measures and nutritional factors) and of elimination (drains, altered metabolism and clearance changes). The higher V d in the initial phase of sepsis has been previously described in studies on aminoglycosides [32,33] and vancomycin [34]. We recently demonstrated an increased V d and a high variability of serum antibiotic concentrations in ICU patients with severe sepsis and septic shock [14].…”
Section: Discussionmentioning
confidence: 68%
“…The influence of mechanical ventilation on the pharmacokinetic of aminoglycoside has been studied in previous study [26]. Ventilation is accompanied by modification of antidiuretic hormone secretion that, in turn, alters the volume of extracellular fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that mechanical ventilation directly affects the pharmacokinetic profile of many pharmaceutical agents, including gentamicin, midazolam, lidocaine, ofloxacin, levofloxacin, dexmedetomidine, cisatracurium, atracurium, propofol, and midazolam. [42][43][44][45][46][47][48] Although data identify the direct result of positive pressure ventilation on altering pharmacokinetic parameters, clinicians have other therapeutic modalities to minimize the effects of these changes. These therapeutic modalities include volume resuscitation, inotropic and vasopressor support, and ventilator management (e.g., lowering tidal volumes and decreasing PEEP).…”
Section: Pharmacokinetic Differences In Patients Receiving Mechanicalmentioning
confidence: 99%